1992
DOI: 10.1017/s0373463300010456
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy and Coverage of Loran-C and of the Decca Navigator System — and the Fallacy of Fixed Errors

Abstract: The proposal to develop an extensive North-West European Loran-C system, replacing many existing chains of the Decca Navigator System (DNS), has led to an intensive debate on the merits of the two navigation aids, especially in the United Kingdom. The paper reviews the principal sources of random and systematic position errors in the two systems. The wide range of DNS random errors, predominantly due to skywave interference, are compared with the Loran-C random errors, and typical coverage limits of acceptable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The DECCA system was based on triangulation from land based radio transmitters. While it is difficult to estimate the magnitude of the positional error, as the accuracy of the DECCA system varies not only with distance from the land-based transmitting station but is also dependant on the season and the time of the day [50] , repeatable accuracies are assumed to be better than 400 m with 95% confidence [51] . With this positional accuracy indicated and the raster resolution of the acoustic data being only 10 m, it is likely that incorrect raster values will have been extracted for the ground-truth samples.…”
Section: Discussionmentioning
confidence: 99%
“…The DECCA system was based on triangulation from land based radio transmitters. While it is difficult to estimate the magnitude of the positional error, as the accuracy of the DECCA system varies not only with distance from the land-based transmitting station but is also dependant on the season and the time of the day [50] , repeatable accuracies are assumed to be better than 400 m with 95% confidence [51] . With this positional accuracy indicated and the raster resolution of the acoustic data being only 10 m, it is likely that incorrect raster values will have been extracted for the ground-truth samples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to control data sets, where point locations were unperturbed, the error treatments were 5, 25, 50, 200 and 400 m. The magnitude of error simulated in this study reflects the possible range of error that may be occurring during various sample techniques. While the smallest error margins are comparable to what might occur using modern positioning systems (Rattray et al 2014), locational uncertainty up to 400 m has been reported in historical data sets, such as where the Decca navigation system was used for positioning (Last 1992;Kubicki & Diesing 2006).…”
Section: Simulated Locational Uncertaintymentioning
confidence: 90%
“…While the smallest error margins are comparable to what might occur using modern positioning systems (Rattray et al . ), locational uncertainty up to 400 m has been reported in historical data sets, such as where the Decca navigation system was used for positioning (Last ; Kubicki & Diesing ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were collected prior to the introduction of the Global Positioning System (GPS) using the Decca Main Chain system and substantial positional errors are to be expected (Kubicki and Diesing, 2006). Repeatable accuracies are assumed to be better than 400 m with 95% confidence (Last, 1992). The samples were collected using a Shipek type sediment grab.…”
Section: Datamentioning
confidence: 99%